2020
DOI: 10.1093/abbs/gmz164
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNA profiling before and after surgery revealed potential diagnostic and prognostic markers for lung adenocarcinoma

Abstract: Exosome is a crucial manner for cancer cell to cell communication and circulating exosomes sever as promising diagnostic and prognostic markers for various types of diseases. A predominant type of cargo of exosome is small RNAs, especially miRNAs. Here, we profiled plasma exosomal miRNAs of six lung adenocarcinoma patients before and after surgery, as well as six healthy individuals as normal control. Our profiling revealed 38 upregulated and 37 downregulated exosomal miRNAs in the plasma of lung adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…miRNA sequencing was performed using plasma exosomes representing all three groups. In total, 159 miRNAs were found to be significantly dysregulated in LA-pre samples vs. healthy volunteers; 24 miRNAs were significantly dysregulated in LA-pre-vs. post-operation; and a further 12 miRNAs showed the same trend, e.g., miR-342-5p (consistent with above study (Xue et al, 2020), miR-574-5p, and miR-222-3p (Han et al, 2020). The AUC values of miR-342-5p and miR-574-5p were both greater than 0.7 (Han et al, 2020).…”
Section: Diagnostic Valuesupporting
confidence: 85%
See 2 more Smart Citations
“…miRNA sequencing was performed using plasma exosomes representing all three groups. In total, 159 miRNAs were found to be significantly dysregulated in LA-pre samples vs. healthy volunteers; 24 miRNAs were significantly dysregulated in LA-pre-vs. post-operation; and a further 12 miRNAs showed the same trend, e.g., miR-342-5p (consistent with above study (Xue et al, 2020), miR-574-5p, and miR-222-3p (Han et al, 2020). The AUC values of miR-342-5p and miR-574-5p were both greater than 0.7 (Han et al, 2020).…”
Section: Diagnostic Valuesupporting
confidence: 85%
“…Plasma exosomal miR-23b-3p, miR-10b-5p, and miR-21-5p were independently associated with poor overall survival (Liu et al, 2017). Kaplan-Meier survival analysis showed that higher expression of miR-151a-5p, miR-10b-5p, miR-192-5p, miR-106b-3p, and miR-484 was associated with a lower survival rate (Xue et al, 2020), implicating them as prognostic biomarker candidates. Survival analysis showed that NSCLC patients with high serum exosomal miR-1246 had shorter OS and DFS than patients with low serum exosomal miR-1246 (Huang and Qu, 2020).…”
Section: Prognostic Valuementioning
confidence: 95%
See 1 more Smart Citation
“…In a study by Xue et al, exosomal miRNA plasma profiling was performed from six lung adenocarcinoma patients before and after surgery. miR-484 was found significantly increased in plasma of lung adenocarcinoma patients compared to controls, but it decreased post-surgery [78].…”
Section: Mirnas Alterations and Cancermentioning
confidence: 86%
“…If NSCLC patients can be found and diagnosed in early stage, there will be more treatment options to ensure better overall survival. Liquid biopsy is a currently promising technology for early diagnosis of NSCLC based on blood contents, such as circulating tumor cells [5], circulating tumor DNA [6], and exosomes [7].…”
Section: Introductionmentioning
confidence: 99%